Characteristics and prognostic analysis of simultaneous bilateral sudden sensorineural hearing loss - Wang, Yingjun; Xiong, Wenping; Sun, Xiao; Duan, Fujia; Lu, Kunpeng; Wang, Haibo; Wang, Mingming (Frontiers in Neurology, 2023)
Objective To evaluate the clinical characteristics of simultaneous bilateral sudden sensorineural hearing loss (Si-BSSNHL) as well as its prognostic factors. Methods Patients with Si-BSSNHL who were admitted to the Department of Otology Medicine between December 2018 and December 2021 were enrolled in the case group. Propensity score matching (PSM) for sex and age was used to select the control group, which included people who had unilateral sudden sensorineural hearing loss (USSNHL) during the same time period. Hearing recovery, audiological examinations, vestibular function assessments, laboratory tests, and demographic and clinical manifestations were analyzed for intergroup comparisons. Binary logistic regressions were used for both univariate and multivariate analyses of Si-BSSNHL prognostic factors. Results Before PSM, the Si-BSSNHL and USSNHL groups differed significantly (p < 0.05) in terms of time from onset to treatment, initial pure-tone average (PTA), final PTA, hearing gain, audiogram curve type, proportion of tinnitus, high-density lipoprotein level, homocysteine level, and effective rate. After PSM, significant differences were also observed in time from onset to treatment, initial PTA, final PTA, hearing gain, total and indirect bilirubin levels, homocysteine level, and effective rate between the two groups (p < 0.05). There was a significant difference in the classification of therapeutic effects between the two groups (p < 0.001). For prognostic analysis, the audiogram curve type was significantly different between the effective group and the ineffective groups of Si-BSSNHL (p = 0.01), in which the sloping type was an independent risk factor for the prognosis of the right ear in Si-SSNHL (95% confidence interval, 0.006–0.549, p = 0.013). Conclusion Patients with Si-BSSNHL had mild deafness, elevated total and indirect bilirubin and homocysteine levels, and poorer prognosis than those with USSNHL. Audiogram curve type was linked to the therapeutic effect of Si-BSSNHL, and the sloping type was an independent risk factor for a poor prognosis in the right ear of Si-SSNHL.